Obituary: Prof. S. George Pemberton, Ph.D., P.Geol., F.R.S.C. - Berita Sedimentologi (Berita Sedimentologi, 2019)
On August 4, 2018, the geological community mourned the passing of Prof. Stuart George Pemberton. Professor Pemberton was most well-known for his remarkable contributions in ichnology that brought Canada to host the world-leading ichnological community. He received a BSc (Honours) in Geology at Queen’s University in Kingston, Ontario (1972) and a MSc (1976) and Ph.D. (1979) in Geology at McMaster University in Hamilton, Ontario.